Effect of intratympanic steroid therapy in sudden sensorineural hearing loss: Our clinical experience - Ahmet Hamdi̇ Kepekci (Medicine Science)
The goal of this study was to assess the efficacy of intratympanic steroid injection (ITS) in reducing irreversible sensorineural hearing loss in patients with sudden sensorineural hearing loss (SSHL). Between February 2018 and February 2024, a total of eighteen patients diagnosed with SSHL and treated with ITS were analyzed in this retrospective study. Hearing levels of all patients were determined before and after treatment. An audiometer from the brand "Interacoustics AD629 Diagnostic Audiometer" was used for audiological assessment. The data was divided into 2 groups, one for midrange frequencies mean (250-500–1000-2000 Hz) and the other for treble frequencies means hearing level (4000-80000Hz), these measures were compared before and after treatment. Hearing levels improved significantly after treatment. Mean midrange frequencies decreased from 44.35±27.23 dB pre-procedure to 35.46±29.49 dB postprocedure (p [Med-Science 2024; 13(4.000): 861-5]